Combining chemotherapy with CAR-T cell therapy in treating solid tumors - Arthur Xuan Wang; Xiao Jing Ong; Criselle D’Souza; Criselle D’Souza; Paul J. Neeson; Paul J. Neeson; Joe Jiang Zhu; Joe Jiang Zhu (Frontiers in Immunology, 2023)
Chemotherapy has long been a standard treatment for a wide range of malignancies, where patients typically undergo multiple rounds of chemotherapy regimens to control tumor growth. In the clinic, the chemotherapy drugs cyclophosphamide and fludarabine are commonly used prior to Chimeric Antigen Receptor T (CAR-T) cell therapy to lymphodeplete and improve CAR-T cell engraftment. In this review, we discuss the use of chemotherapy in combination with CAR-T cell therapy. We also show that chemotherapy can deplete immunosuppressive cells, promote a pro-inflammatory tumor microenvironment, disrupt tumor stroma, and improve CAR-T cell recruitment to the tumor. Although the combination of chemotherapy plus CAR-T cell therapy is promising, certain aspects of chemotherapy also pose a challenge. In addition, the combined therapeutic effect may be heavily dependent on the dose and the treatment schedule. Thus, we also discussed the obstacles to effective clinical outcomes of the combination therapy.